Hubungan Edukasi Kesehatan Terhadap Pengetahuan Bahaya Pergaulan Bebas dan Narkoba Pada Siswa SMA Negeri 8 Tangerang Selatan - Djimmy Heru Purnomo Babo; Erna Juliana Simatupang; Eka Widya Rita Panjaitan; Evelyn Sumihar Friyanti; Maria Ernestha Djemu Laga (CV. ALIM'SPUBLISHING, 2025)
Adolescence is a crucial stage in a person's life that is characterized by various changes. This period is characterized by high curiosity about various things, including promiscuity and drug abuse issues. This research is intended to overcome a number of challenges in increasing public awareness and knowledge, especially among adolescents, about the dangers of promiscuity and drug abuse at SMA Negeri 8 South Tangerang. This research design used the Quasi Experiment method with the One Group Pre Test-Post Test design. This research was conducted at SMA Negeri 8 South Tangerang in October 2024. The sampling technique applied was non-probability sampling technique and the sample used consisted of 32 students from SMA Negeri 8 South Tangerang. It can be seen that the average value of the difference in knowledge before and after the provision of health education is 24.53, with a standard deviation of 12.139, and obtained a Sig. (2-tailed) value of 0.000. It can be concluded that, overall, the activities of providing education through health counseling for students of SMA Negeri 8 South Tangerang regarding the dangers of promiscuity and drugs show positive results. Keywords: Adolescents, Drugs, Education, Promiscuity.